Utilization of Heat from Geothermal Well Pipes as Electricity for Road Lighting Based on The Internet of Things - Rizani Firdaus; Muhamad Ariandi (Advance Sustainable Science Engineering and Technology, 2023)
PT. Pertamina Geothermal Energy Area Lumut Balai has a very extreme work location with various contours, safety factors and lack of access to electricity for street lighting are things that need attention given the importance of street lighting in the company's operations. Street lighting is an important element that supports the comfort and safety of road users in their activities at night. The research objective is to design an IoT (Internet Of Things) system that can monitor the utilization of pipe heat into electrical energy for street lighting and provide street lighting needs around geothermal well pipes. In this study used thermoelectric as a tool to generate electrical energy from available heat. The IoT system is used to read data parameters as a tool to display temperature, voltage and current values on the LCD (Liquid Crystal Display) and the Thingspeak website. The temperature value is read by the MAX6675 thermocouple sensor while the INA219 sensor is used to read the voltage and current values. The focus of this research is to heat the thermoelectric so that it can produce electrical energy to turn on the lights as lighting and can monitor parameter data directly. The highest thermoelectric electrical energy output is at a temperature of 75.1˚C. Where at this temperature a voltage of 2.32 V is generated and a current of 0.03 A. The lamp will turn on if the thermoelectric heat is fulfilled. The light turns on when the environment is dark and the light turns off when the environment is bright